Pemahaman Orang Tua di Komplek Griya Permata Asri tentang Pentingnya Pembentukan Karakter Anak Usia Dini: parents' understanding in the Griya Permata Asri Complex on the Importance of Early Chilhood Character Formation - Oktaviana, Safira; Hanafi, Syadeli; Rosmilawati, Ila (Innovative: Journal Of Social Science Research, 2025)
This study aims to understand parents’ comprehension, awareness of their role, and the values that need to be instilled in the character building of early childhood children in the Griya Permata Asri Complex. The research uses a descriptive qualitative method with data collection techniques through interviews and observations. The researcher conducted interviews with 7 parents (fathers and mothers who have children aged 0-6 years). The results show that the majority of parents in the Griya Permata Asri Complex have a fairly good understanding of the importance of character building from an early age. This is reflected in the awareness and responsibility held by parents as the first and primary educators. In educating their children, parents use approaches such as habituation, modelling, and advice, in accordance with the child’s developmental stages. The values most frequently instilled by parents include honesty, responsibility, politeness, independence, religiosity, and cleanliness. Keywords: Character building, Parents’ understanding, Early childhood, Character education